Identifikasi Orthoptera di Area Persawahan Desa Ngabean Keecamatan Secang sebagai Buku Referensi: (Identification of Orthoptera in the Rice Fields of Ngabean Village, Secang District as a Reference Book) - Yuliyati, Safira; Permadani, Karunia Galih; Prajoko, Setiyo (BIODIK, 2024)
Rice fields are one of the most important ecosystems because rice fields can produce staple food which is very important for humans. The condition of the rice fields in Ngabean Village, Secang District, is where many Orthoptera are found. The potential of the environment can be used as a learning resource, but currently it is still not optimal. The unidentification of Orthoptera in the rice fields of Ngabean Village, Secang District is something that has the potential to be developed. So it is necessary to identify the Orthoptera order in the rice fields in Ngabean Village, Secang District as a reference book. This research aims to determine the results of Orthoptera identification, the abiotic factors that influence it, and the feasibility of the biology reference book being developed. This research uses mixed method research which is divided into two stages, namely exploratory qualitative research and Research and Development (R&D) development research with the 4-D development model. However, this research only reached the third stage, namely develop. Data collection was carried out by Ortopthera exploration in the rice fields of Ngabean Village, Secang District. Analysis of the feasibility of reference books was carried out with validation from material experts and media experts. Apart from that, readability tests were carried out by entomology lecturers and students. The research results found 15 species of Orthopthera. The reference book developed as a learning resource for students obtained an average validation result of 69.63% which was included in the appropriate category. Apart from that, the percentage of readability of reference books by students was 87.99% in the high category. Abstrak. Sawah merupakan salah satu ekosistem terpenting karena sawah dapat menghasilkan bahan makanan pokok yang sangat penting bagi manusia. Kondisi persawahan di Desa Ngabean Kecamatan Secang banyak dijumpai Orthoptera. Potensi lingkungan dapat digunakan sebagai sumber belajar namun saat ini masih kurang maksimal. Belum diidentifikasinya Orthoptera di area persawahan Desa Ngabean Kecamatan Secang menjadi hal yang potensial dikembangkan. Sehingga diperlukan adanya identifikasi ordo Orthoptera area persawahan di Desa Ngabean Kecamatan Secang sebagai buku referensi. Penelitian ini bertujuan untuk mengetahui hasil identifikasi Orthoptera, faktor abiotik yang mempengaruhinya, dan kelayakan buku referensi biologi. Penelitian ini menggunakan penelitian mixed method yang terbagi menjadi dua tahap yaitu penelitian kualitatif jenis eksploratif dan penelitian pengembangan Research and Development (R&D) dengan model pengembangan 4-D. Namun pada penelitian ini hanya sampai tahap ketiga yaitu develop. Pengumpulan data dilakukan dengan eksplorasi Ortopthera di area persawahan Desa Ngabean Kecamatan Secang. Analisis kelayakan buku referensi dilakukan dengan validasi ahli materi dan ahli media. Selain itu, dilakukan uji keterbacaan oleh dosen entomologi dan mahasiswa. Hasil penelitian ditemukan 15 spesies Ortopthera. Buku referensi yang dikembangkan sebagai sumber belajar memperoleh hasil validasi rata-rata 69,63% dengan kategori layak. Persentase keterbacaan buku referensi oleh mahasiswa diperoleh hasil sebesar 87,99 % dengan kategori tinggi.